HUBUNGAN KECEMASAN DENGAN PEMAHAMAN KONSEP MATEMATIKA DAN SISWA - Munasiah, Munasiah (ARITHMETIC: Academic Journal of Math, 2020)
Understanding mathematical concepts are the first key in understanding the material because there is a link between one concept with another concept. The implementation of learning is expected to link mathematical concepts in everyday life. Internal and external factors of students are very influential in mathematics learning, one of them is mathematics anxiety. Mathematics anxiety that is processed by students well can make these students enthusiastic to learn mathematics, but conversely, if students are not able to process mathematics anxiety properly it will negatively affect mathematics learning outcomes. The purpose of this study was to determine how much influence mathematics anxiety has on understanding mathematical concepts. This research is a descriptive quantitative research.  The method used in this study is a survey method using questionnaires and questions in collecting data. The results of this study indicate that mathematics anxiety harms understanding mathematical concepts, with low chorea values. It can be interpreted that in this case, the respondent has not been able to process mathematics anxiety into motivation to continue learning to understand mathematical concepts. So anxiety has a significant effect on understanding mathematical concepts. From this research it is hoped that it can be used as a teacher's reference in carrying out mathematics learning, teachers can help reduce student anxiety by using learning models that are fun and effective, and teachers can provide motivation to students who experience mathematics anxiety.